Remedying the fractured domain through slow journalism: A case of journalistic podcasting in India. Issue 1 (May 2023) - Mehendale, Sneha Gore; Jaggi, Ruchi Kher
This study contributes significantly by adding to the limited existing knowledge of news podcasting practices as well as building an empirical understanding of a specific type of slow journalism. It examines the practices of news podcasting in India and positions it as a form of slow journalism. The study found that this construction of slow journalism through podcasting is purposeful on the journalist's part. More importantly, it is done with the intention of remedying the systemic fractures that contemporary journalism experiences. Finally, reclaiming the lost trust in journalism through practicing slow journalism is one of the crucial aims that podcasting journalists have in this context. The data for this paper was collected through newsroom observations and in-depth interviews with podcasting journalists across three Indian newsrooms. The study reveals the specific features of the news selection and production practices of the podcasting journalists fitting in the slow journalism framework, as told through their own perspectives as practitioners.